ANALISIS EKSTRAK ETANOL DAUN GAHARU (Aquilaria malaccensis) TERHADAP PENEBALAN ALVEOLI DAN LEUKOSIT DIFERENSIAL MENCIT (Mus musculus) YANG DI INDUKSI KARBAMAT SECARA IN VIVO - Pratama, Mohammad Indra; Jailani, Jailani; Nasution, Ruqoyyah; Awang Sari, Eadvin Rodrinda; Pribadi, Teguh (BIOEDUKASI (Jurnal Pendidikan Biologi), 2024)
The research aimed to look at the effect of induction. The effect of administering ethanol extract of gaharu leaves (Aquilaria malaccensis Lamk) on the histopathological picture of the lungs of white mice (Mus musculus) induced by carbamate class insecticides. The method used was truly experimental, carbamate induction via the intramuscular route with a dose of 14.4 Mg/BW and agarwood extract administered via the oral route with doses of 100, 200, and 300 Mg/BW, the duration of each treatment was 15 days. After treatment, preparations were made of the lungs using the paraffin block staining method with hematoxylin-eosin, the thickness of the alveolar septa and the presence of alveolar macrophages were measured. The results of the research showed that there was a thickening of the alveolar septa after induction of carbamate insecticide at a dose of 14.4 mg/BW with an average thickness of 21.62 µm compared to the healthy control group of 12.61, in addition to an increase in the percentage of neutrophils of 48.66 compared to the healthy controls of 23.33 which was caused by inflammation in the mice's bodies. , a decrease in the thickness of alveolar septa was caused by the administration of ethanol extract of agarwood leaves at a dose of 100/200/300 mg/BW with an average thickness of 15.18, 13.73, 15.57 µm compared to the negative control of 21.62 µm. Thus, it can be concluded that there is an influence of agarwood leaf extract on lung histopathology -lungs of mice induced with carbamate class insecticides.